Fatores associados ao nascimento pré-termo em Campina Grande, Paraíba, Brasil: um estudo caso-controle Factors associated with preterm birth in Campina Grande, Paraíba State, Brazil: a case-control study - Paula Lisiane Assunção; Hillegonda Maria Dutilh Novaes; Gizelton Pereira Alencar; Adriana Suely de Oliveira Melo; Marcia Furquim de Almeida (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2012)
Estudo caso-controle (2008-2009) de base populacional que analisou fatores de risco para nascimento pré-termo em Campina Grande, Paraíba, Brasil. Foram incluídos 341 nascimentos pré-termo e 424 controles. Utilizou-se regressão logística múltipla. Foram fatores de risco: idade materna de 35 ou mais (OR = 2,00; IC95%: 1,00-4,03), pré-termo prévio (OR = 2,32; IC95%: 1,25-4,29), pré-natal inadequado (OR = 2,15; IC95%: 1,40-3,27), ganho ponderal materno insuficiente (OR = 2,33; IC95%: 1,45-3,75), dano físico materno (OR = 2,10; IC95%: 1,22-3,60), hipertensão arterial com eclampsia (OR = 17,08; IC95%: 3,67-79,43) e sem eclampsia (OR = 6,42; IC95%: 3,50-11,76), internação (OR = 5,64; IC95%: 3,47-9,15), alteração do volume amniótico (OR = 2,28; IC95%: 1,32-3,95); sangramento vaginal (OR = 1,54; IC95%: 1,01-2,34) e gestação múltipla (OR = 22,65; IC95%: 6,22-82,46). Elevada e homogênea prevalência de pobreza e baixa escolaridade pode ter contribuído para que as variáveis socioeconômicas não permanecessem com associação significativa para o nascimento pré-termo. A case-control study (2008-2009) analyzed risk factors for preterm birth in the city of Campina Grande, Paraíba State, Brazil. A total of 341 preterm births and 424 controls were included. A multiple logistic regression model was used. Risk factors for preterm birth were: previous history of preterm birth (OR = 2.32; 95%CI: 1.25-4.29), maternal age (OR = 2.00; 95%CI: 1.00-4.03), inadequate prenatal care (OR = 2.15; 95%CI: 1.40-3.27), inadequate maternal weight gain (OR = 2.33; 95%CI: 1.45-3.75), maternal physical injury (OR = 2.10; 95%CI: 1.22-3.60), hypertension with eclampsia (OR = 17.08; 95%CI: 3.67-79.43) and without eclampsia (OR = 6.42; 95%CI: 3.50-11.76), hospitalization (OR = 5.64; 95%CI: 3.47-9.15), altered amniotic fluid volume (OR = 2.28; 95%CI: 1.32-3.95), vaginal bleeding (OR = 1.54; 95%CI: 1.01-2.34), and multiple gestation (OR = 22.65; 95%CI: 6.22-82.46). High and homogeneous prevalence of poverty and low maternal schooling among both cases and controls may have contributed to the fact that socioeconomic variables did not remain significantly associated with preterm birth.